Accuracy of rib palpation for dry needling of deep periscapular musculature, measured with ultrasound. (April 2021) - Cushman, Daniel M.; Scholl, Linda Vernon; Ludlow, Monica; Cunningham, Shellie; Teramoto, Masaru
Abstract: Introduction: Dry needling of the periscapular musculature is a procedure commonly performed by physical therapists. Needling of the deep musculature may be challenging, and use of a thoracic rib as a "backstop" is often applied to prevent inadvertent puncture of the pleura. The aim of this study was to: 1) To examine the accuracy rate of experienced physical therapists in identifying a mid-scapular thoracic rib using palpation, 2) to understand patient characteristics that affect the accuracy rate, and 3) to examine if therapist confidence levels were associated with palpatory accuracy. Methods: Two experienced physical therapists attempted to palpate a thoracic rib in the mid-scapular region of healthy participants (n = 101 subjects, 202 ribs), and self-reported their level of confidence in an accurate palpation. Their accuracy was verified with ultrasonography. Results: The two physical therapists were accurate on 73.3% of palpations and did not differ in accuracy (72.0% vs. 75.0%, p = 0.747). The only ultrasonographic or subject characteristic measurement that correlated with improved accuracy was a reduced muscle thickness (p = 0.032). Therapists' self-reported confidence levels did not correlate to actual accuracy (p = 0.153). Discussion: Physical therapists should be aware that palpation of a thoracic rib may not be as accurate as it may seem. The greater thickness of muscle in the area reduces the accuracy of accurate palpation. Conclusion: Dry needling of the periscapular muscles should be done with caution if using a rib as a "blocking" technique.